Quantifying the impact of the Public Health Responsibility Deal on salt intake, cardiovascular disease and gastric cancer burdens: interrupted time series and microsimulation study. Issue 9 (18th July 2019) - Laverty, Anthony A; Kypridemos, Chris; Seferidi, Paraskevi; Vamos, Eszter P; Pearson-Stuttard, Jonathan; Collins, Brendan; Capewell, Simon; Mwatsama, Modi; Cairney, Paul; Fleming, Kate; O'Flaherty, Martin; Millett, Christopher
Abstract : Background: In 2011, England introduced the Public Health Responsibility Deal (RD), a public-private partnership (PPP) which gave greater freedom to the food industry to set and monitor targets for salt intakes. We estimated the impact of the RD on trends in salt intake and associated changes in cardiovascular disease (CVD) and gastric cancer (GCa) incidence, mortality and economic costs in England from 2011–2025. Methods: We used interrupted time series models with 24 hours' urine sample data and the IMPACTNCD microsimulation model to estimate impacts of changes in salt consumption on CVD and GCa incidence, mortality and economic impacts, as well as equity impacts. Results: Between 2003 and 2010 mean salt intake was falling annually by 0.20 grams/day among men and 0.12 g/d among women (P-value for trend both < 0.001). After RD implementation in 2011, annual declines in salt intake slowed statistically significantly to 0.11 g/d among men and 0.07 g/d among women (P-values for differences in trend both P < 0.001). We estimated that the RD has been responsible for approximately 9900 (interquartile quartile range (IQR): 6700 to 13, 000) additional cases of CVD and 1500 (IQR: 510 to 2300) additional cases of GCa between 2011 and 2018. If the RD continues unchanged between 2019 and 2025, approximately 26 000 (IQR: 20 000 to 31, 000) additional cases of CVD and 3800 (IQR: 2200 to 5300) cases of GCa may occur. Interpretation: Public-private partnerships such as the RD which lack robust and independent target setting, monitoring and enforcement are unlikely to produce optimal health gains.